LONELINESS CONTRIBUTES TO PSYCHOLOGICAL WELL BEING OF WOMEN APPROACHING MENOPAUSE - Dirgahayu, Inggrid; Rustikayanti, Raden Nety; Novianti, Wini Resna; Jayanti, Tri Nur (Karsa Husada Health Institute Garut, 2023)
Psychological Well-Being describes individual functioning through self-acceptance. At every stage of human development, there will be changes both physically and psychologically that require a process of self-adjustment. Women approaching menopause are considered as women heading towards premature aging. During the phase before menopause a woman will feel the signs of menopause which vary depending on the amount of estrogen levels in the body. One of the prominent psychological complaints during menopause is loneliness. A subjective experience experienced by individuals when hopes and expectations regarding an interpersonal relationship do not match reality. This experience is often felt by women approaching menopause. The study aims to analyse the relationship between loneliness and psychological well being. The research method used is correlational with a cross sectional approach in 100 female populations approaching menopause. The sample technique used was purposive sampling. The research instruments consisted of the UCLA Loneliness Scale Version 3 and RYFF'S Pyschological Well-Being. Statistical analysis used with Pearson correlation test (Product Moment). The independent variable in this research is loneliness, while the dependent variable is the psychological well being of women approaching menopause. The results showed that there was a significant relationship between Lonelinees and Psycological well being of women before menopause. Women before menopause who have a high level of psychological well being, almost all are in a low level of loneliness. These results are in accordance with the theory that psychological well being will affect the way a person interacts and socialises, and this will affect one's behaviour as well as one's level of loneliness. If someone with good Psychological Well being eats the level of Loneliness in women approaching menopause will be low.